Propensity to Leave: A Preliminary Examination of March and Simon’s Model - Anderson, John C.; Milkovich, George (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1980)
March and Simon's (1958) model of the decision to participate was examined empirically with a sample of professional, managerial and technical employees. The results provide partial support for the model. While confirming the importance of job satisfaction in predicting the propensity to leave, perceived ease of movement, intraorganizational movement possibilities, and the interaction of job dissatisfaction and ease of movement were also found to be significant independent contributors in explaining the employee’s propensity to leave.